Connections between knowledge organisation and social cohesion in information science - Moreira, Walter [UNESP]; Redigolo, Franciele Marques [UNESP]; Silva, Amanda Mendes da [UNESP] (Univ Zaragoza, 2024)
Knowledge organization systems (KOS) are based on functions and ethical aspects that contribute to building social cohesion as instruments that shape worldviews and organize community memory. Therefore, it is necessary to qualify both access and use of information mediated by documentary representations based on KOS such as documentary languages in institutions such as libraries. In this sense, the following research problems arise: a) what are the connections between the functions and purposes of KOS and social cohesion; b) how has Information Science literature incorporated and discussed the concept of social cohesion? c) if there are such discussions, are there connections with KOS? This research aims to investigate the Information Science literature about the theoretical and applied connections between the organization of knowledge, knowledge organization systems, and the concept of social cohesion. This research is qualitative and exploratory and uses the content analysis model (Bardin, 2003). The databases used to collect the articles were the Information Science Database (BRAPCI), Web of Science (WoS), and Library, Information Science and Technology Abstracts (LISTA). Through applying the criteria and analysis, it was possible to see that the retrieved articles discreetly address the relationship between social cohesion and Information Science and peripherally the relationship between Knowledge Organization and KOS.
Keywords: Information Science; Knowledge organization; Knowledge organization systems; Social cohesion